1941
DOI: 10.1177/004051754101100901
|View full text |Cite
|
Sign up to set email alerts
|

The Rôle of Cystine in the Structure of the Fibrous Protein, Wool

Abstract: Wool is remarkable among textile materials in that it possesses high extensibility and the ability to return to its original length or shape after being stretched or distorted. These properties are of advantage in such products as clothing, blankets, and carpets. It is shown that a number of the important physical properties as well as some of the chemical properties of wool are dependent upon a unique molecular structure, provided by the presence of disulfide or cystine cross-linkages between the main molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1942
1942
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Goddard & Michaelis. [1934; 1935] found that wool was dissolved by strongly alkaline solutions of thiolacetic acid owing to the complete reduction ofthe disulphide-S. Patterson, Geiger, Mizell & Harris [1941] have studied the reduction of the disulphide-S of wool with solutions of thiolacetic acid of low acidities and it is of interest to compare the extent of disulphide reduction which they obtained' with our results. These workers reduced wool in buffer solutions of thiolacetic acid.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Goddard & Michaelis. [1934; 1935] found that wool was dissolved by strongly alkaline solutions of thiolacetic acid owing to the complete reduction ofthe disulphide-S. Patterson, Geiger, Mizell & Harris [1941] have studied the reduction of the disulphide-S of wool with solutions of thiolacetic acid of low acidities and it is of interest to compare the extent of disulphide reduction which they obtained' with our results. These workers reduced wool in buffer solutions of thiolacetic acid.…”
supporting
confidence: 53%
“…It thus appeared probable that thiolacetic acid reduced about 2*0 % disulphide-S under the conditions used by Patterson et al [1941]. In order to find out whether the disulphide-S reduced belonged to fractions A and B, a sample of our wool was immersed for 18 hr.…”
mentioning
confidence: 99%
“…In the cysteine solutions slight softening of the fibres was detected at pH 10.0 and 10.5. The form of the pH-thioglycollate reduction curve is similar to that reported by Patterson et al (1941) although, because of the milder conditions employed, the extent of reduction is less. The formation of sulphydryl groups in the presence of potassium cyanide has been confirmed by increasing the concentration of this reagent to 1.0M, adjusting the pH value to 10.5, and incubating as before for 1 hr.…”
supporting
confidence: 80%
“…However, it was subsequently shown [6] that few if any free sulfhydryl groups are present in the alkali-treated wool even prior to hydrolysis. In addition, this hypothesis, when applied to wool, would result in the rupture of the disulfide cross-links, a process which would be expected to yield a material of very low strength and extremely high alkalisolubility [7]. Yet samples of wool, treated with alkali by methods described elsewhere, exhibited relatively high strengths and low alkali-solubilities (see table 1).…”
Section: Oh Ohmentioning
confidence: 99%
“…A sodium nitroprusside test, used for the qualitative detection of sulfhydryl groups, was negative on both samples. Immediately after the washing treatment, small portions of the wools were treated with benzyl chloride [7] in order to combine any cysteine residues that might be present.…”
Section: Experimental Procedures 1 Preparation Of Alkali-treated mentioning
confidence: 99%